Pasta Kalsium Hidroksida Sebagai Bahan Dressing pada Perawatan Trauma Insisif Permanen Imatur - Puspitasari, Wita; Pratidina, Naninda Berliana; Riyanti, Eriska (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2022)
Extrusive luxation is an outward or incisal displacement of teeth due to trauma with long- term complications, namely pulpal necrosis and periapical inflammation. Endodontic treatment that can be performed on immature permanent incisor is regenerative endodontics or apexification. The aim of this case report is to evaluate the effectiveness of calcium hydroxide paste as a dressing material in regenerative endodontic treatment. A 7 year old girl patient was brought by his mother to the Children's Dental Polyclinic at RSGM UNPAD with complaints that the front maxillary teeth touched the ground. The results of the clinical examination showed that tooth 11 was extruded by 4 mm and had a mobility level of 2 and the gums were swollen and exposed labial to apical third. The treatment carried out was fixation and orthodontic treatment but after 6 months of treatment tooth 11 returned to extrusion. Radiograph showed radiolucency in periapical region 11, negative vitality test, grade 1 mobility test and 4 mm probe test in mid-buccal region. The treatment performed is regenerative endodontics. Currently, patients use calcium hydroxide paste as a dressing material to treat periapical abscesses. After 3 months of treatment, from the patient's periapical X-ray, it can be seen that the radiolucent appearance in the periapical area has begun to decrease. Calcium Hydroxide Paste is an effective dressing material for regenerative endodontic treatment of immature permanent incisor with dentoalveolar trauma.